A Debated but Little Examined Mathematical Text: Papyrus Berlin 6619 - Miatello, Luca (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
This paper proposes an updated analysis of the four mathematical problems on the two main fragments of P. Berlin 6619. Photographs, transcription, translation and commentary of the problem texts are included. The analysis focuses in particular on problem 1, on the recto of the large fragment, previously interpreted as the calculation of the sides of two squares. The sentence jr.t HAy.t m wa r nHH (...) indicates that the problem concerns the calculation of two sides of a rectangle. This interpretation is supported also by architectural and cross-cultural parallels.